Cocaine-Induced Synaptic Redistribution of NMDARs in Striatal Neurons Alters NMDAR-Dependent Signal Transduction - Delint-Ramirez, Ilse; Segev, Amir; Pavuluri, Asha; Self, David W.; Kourrich, Saïd (Frontiers in Neuroscience, 2020)
The consequence of repeated cocaine exposure and prolonged abstinence on glutamate receptor expression in the nucleus accumbens has been extensively studied. However, the early effects of cocaine on NMDAR signaling remain unknown. NMDAR signaling depends on the subunit composition, subcellular localization and the interaction with proteins at the postsynaptic density (PSD), where NMDARs and other proteins form supercomplexes that are responsible for the signaling pathways activated by NMDAR-induced Ca2+ influx. Here, we investigated the effect of cocaine on NMDAR subunit composition and subcellular localization following both intraperitoneal non-contingent cocaine and response-contingent intravenous cocaine self-administration in mice. We found that repeated cocaine exposure, regardless of the route or contingency of drug administration, decreases NMDAR interactions with the PSD and synaptic lipid rafts in the accumbens shell and dorsal striatum. We provide evidence that cocaine triggers an early redistribution of NMDARs from synaptic to extrasynaptic sites, and that this adaptation has implications in the activation of downstream signaling pathways. Thus, consistent with a loss of NMDAR function, cocaine-induced ERK phosphorylation is attenuated. Because early NMDAR activity contributes to the initiation of lasting addiction-relevant neuroadaptations, these data may hold clues into cellular mechanisms responsible for the development of cocaine addiction.